APPLICATION OF THE PROJECT METHOD TO IMPROVE NATURALIST INTELLIGENCE AND INTERPERSONAL INTELLIGENCE OF CHILDRE (Study In Group B PAUD Budi Mulya Kabupaten Bengkulu Selatan) - Rici Oktari; Nina Kurniah (DIADIK, 2019)
Study of the application of project methods to improve Naturalist Intelligence and Interpersonal Intelligence for Group B early childhood. This research is a Classroom Action Research (CAR) study with a chemistry and Mc Taggaet research model consisting of planning, action, observation Observe) and reflection (Reflect), in the implementation carried out for 3 cycles with research subjects in group B children at Budi Mulya PAUD South Bengkulu Regency, totaling 15 children, namely 2 girls and 13 boys. The data collection technique of this study used observations and analyzed using percentages and averages for knowing improvement between cycles using t-test analysis ("t" test). Based on the results of the study it can be concluded that the project method can significantly improve children's naturalist and interpersonal intelligence.